Meningkatkan Life Skill pada Anak Down Syndrome dengan Teknik Modelling - Rina, Amherstia Pasca (Persona:Jurnal Psikologi Indonesia, 2016)
The purpose of this research is to improve life skills in children with Down syndromeby using modeling techniques. Subjects in this study 1 children. Subject (S) is a boy aged 11years. Asesment results show that the subject has the characteristics of Down syndrome, has thecognitive abilities that are categorized as moderate mental retardation, difficulty coordinatingmovement of the eyes and hands, as well as the ability of life skills is low. The results showedthat the intervention modeling techniques can improve life skills in the subject. Behavioraltherapy with modeling techniques provide a change to the subject in a positive though notoptimal. Modeling techniques can not complete the whole subject matter related to the subjectemotional state and parenting parentsKeywords : Life Skill, Down Syndrome, Modelling Technique